2021
DOI: 10.1055/a-1541-7659
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection vs. endoscopic mucosal resection for early Barrett's neoplasia in the West: a retrospective study

Abstract: Background The difference in clinical outcomes after endoscopic submucosal dissection (ESD) and endoscopic mucosal resection (EMR) for early Barrett's esophagus (BE) neoplasia remains unclear. We compared the recurrence/residual tissue rates, resection outcomes, and adverse events after ESD and EMR for early BE neoplasia. Methods We included patients who underwent EMR or ESD for BE-associated high grade dysplasia (HGD) or T1a esophageal adenocarcinoma (EAC) at eight academic hospitals. We compared de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 32 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…ESD has become the standard of care for the resection of esophageal squamous cell neoplasia and gastric adenocarcinoma, considering the virtual local recurrence rate, but also the optimal histological analysis allowed by an en bloc-resected specimen [21]. While an underpowered randomized controlled trial demonstrated the absence of clinical benefit of ESD in the routine management of early Barrett’s neoplasia [22], a number of large retrospective studies confirmed the safety of ESD in this indication with 89%–93% en bloc, 73%–79% R0, and 65%–66% curative resection rates, at the cost of 0%–1.5% perforations, 1.4–2.1% delayed bleeding, and 2.1%–16% stricture rates [23-25]. Thus, the safety profile is similar to EMR, with a possible benefit in terms of histological analysis of esophageal adenocarcinomas [5], but longer procedural times (over 60 mn in most publications).…”
Section: Endoscopic Treatment Of Barrett’s Esophagusmentioning
confidence: 99%
“…ESD has become the standard of care for the resection of esophageal squamous cell neoplasia and gastric adenocarcinoma, considering the virtual local recurrence rate, but also the optimal histological analysis allowed by an en bloc-resected specimen [21]. While an underpowered randomized controlled trial demonstrated the absence of clinical benefit of ESD in the routine management of early Barrett’s neoplasia [22], a number of large retrospective studies confirmed the safety of ESD in this indication with 89%–93% en bloc, 73%–79% R0, and 65%–66% curative resection rates, at the cost of 0%–1.5% perforations, 1.4–2.1% delayed bleeding, and 2.1%–16% stricture rates [23-25]. Thus, the safety profile is similar to EMR, with a possible benefit in terms of histological analysis of esophageal adenocarcinomas [5], but longer procedural times (over 60 mn in most publications).…”
Section: Endoscopic Treatment Of Barrett’s Esophagusmentioning
confidence: 99%
“…Nevertheless, there is evidence that ESD is associated with an increased incidence of complications, including hemorrhage, perforation, and postoperative stricture of the esophagus because of the complex surgical procedures 26 . So far, a number of studies have shown that ESD is safer than EMR in treating early‐stage esophagus carcinoma, but their findings are inconsistent with each other 27–29 . As far as we know, no specific comparison between ESD and EMR systems has been conducted with specific comparisons between ESD and EMR in treating early‐stage carcinoma of esophagus.…”
Section: Introductionmentioning
confidence: 99%
“… 26 So far, a number of studies have shown that ESD is safer than EMR in treating early‐stage esophagus carcinoma, but their findings are inconsistent with each other. 27 , 28 , 29 As far as we know, no specific comparison between ESD and EMR systems has been conducted with specific comparisons between ESD and EMR in treating early‐stage carcinoma of esophagus. To establish a clinical basis for treating superficial esophagus carcinoma under endoscopy, a meta trials were conducted to assess the impact of ESD and EMR in wound complication on early stages of esophagus carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic resection, with endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD), is the mainstay of management of early esophageal neoplasia 1 . While early adverse events (AEs) such as bleeding or perforations occur infrequently ( < 2 %), post-endoscopic esophageal strictures remains a concern in 10 % to 20 % of patients 2 3 . Post-endoscopic esophageal strictures occur in up to 90 % of the patients when the resected circumference exceeds 75 % of the esophageal lumen 4 5 6 ; however, the pathophysiology of these strictures is poorly understood.…”
Section: Introductionmentioning
confidence: 99%